LUTEINIZING HORMONE TO FOLLICLE STIMULATING HORMONE RATIO IN PATIENTS WITH POLYCYSTIC OVARY SYNDROME - Khattak, Madiha; Sultana, Nuzhat; Usman, Robina; Khattak, Umama; Zafar, Umema; Salman, Henna (Journal of Ayub Medical College Abbottabad, 2020)
Background: Polycystic ovary syndrome is the most commonly occurring endocrinopathy in females of reproductive age group. It is characterized by a wide range of signs and symptoms resulting from hormonal derangements leading to reduced fertility. Methods: This was a cross-sectional (comparative) study. We took 40 cases of polycystic ovary syndrome and 40 controls of infertility without polycystic ovary syndrome depending on the presence of clinical features and ultrasound scans. Blood samples were collected and assayed for luteinizing hormone and follicle stimulating hormone. Data was analyzed with SPSS-19. Results: Luteinizing hormone to follicle stimulating hormone ratio was raised in 3 out of 35 patients (8%) in cases and in 2 out of 39 patients (5%) in controls. There was no statistically significant difference in the luteinizing hormone levels and the follicle stimulating hormone levels and the luteinizing hormone to follicle stimulating hormone ratio of the two groups as indicated by a p-value> 0.05. Conclusion: Luteinizing hormone to follicle stimulating hormone ratio was not found to be raised in majority of the polycystic ovary syndrome patients included in this study. Keywords: Polycystic Ovary Syndrome; Luteinizing Hormone; Follicle Stimulating Hormone; Infertility